Genome of a citrus rootstock and global DNA demethylation caused by heterografting. (1st April 2021) - Huang, Yue; Xu, Yuantao; Jiang, Xiaolin; Yu, Huiwen; Jia, Huihui; Tan, Chunming; Hu, Gang; Hu, Yibo; Rao, Muhammad Junaid; Deng, Xiuxin; Xu, Qiang
Abstract: Grafting is an ancient technique used for plant propagation and improvement in horticultural crops for at least 1, 500 years. Citrus plants, with a seed-to-seed cycle of 5–15 years, are among the fruit crops that were probably domesticated by grafting. Poncirus trifoliata, a widely used citrus rootstock, can promote early flowering, strengthen stress tolerance, and improve fruit quality via scion–rootstock interactions. Here, we report its genome assembly using PacBio sequencing. We obtained a final genome of 303 Mb with a contig N50 size of 1.17 Mb and annotated 25, 680 protein-coding genes. DNA methylome and transcriptome analyses indicated that the strong adaptability of P. trifoliata is likely attributable to its special epigenetic modification and expression pattern of resistance-related genes. Heterografting by using sweet orange as scion and P. trifoliata as rootstock and autografting using sweet orange as both scion and rootstock were performed to investigate the genetic effects of the rootstock. Single-base methylome analysis indicated that P. trifoliata as a rootstock caused DNA demethylation and a reduction in 24-nt small RNAs (sRNAs) in scions compared to the level observed with autografting, implying the involvement of sRNA-mediated graft-transmissible epigenetic modifications in citrus grafting. Taken together, the assembled genome for the citrus rootstock and the analysis of graft-induced epigenetic modifications provide global insights into the genetic effects of rootstock–scion interactions and grafting biology.